Tetrandrine slows disease progression on high-resolution computed tomography and lung function decline in artificial stone-associated silicosis: a retrospective cohort study - Shaowei Zhou; Jin Shi; Zidan Chen; Luqin Bian; Limin Huang; Ling Mao (BMC Pulmonary Medicine)
Abstract Background Silicosis, a progressive fibrotic lung disease caused by silica dust inhalation, is a significant occupational health concern, particularly among artificial quartz stone workers. Tetrandrine, a bisbenzylisoquinoline alkaloid, is the only plant-derived drug approved for the treatment of silicosis in China. The present study aimed to evaluate the efficacy of tetrandrine in slowing the progression of artificial stone-associated silicosis. Methods In this retrospective cohort study, patients were divided into an observation group (n = 53), which received tetrandrine (60 mg, 3 times daily for 6 consecutive days, followed by a 1-day break, with each cycle lasting 3 months), and a control group (n = 26), which received only symptomatic treatment. High-resolution computed tomography (HRCT) and pulmonary function tests (PFTs) were performed at baseline and after 12 months of treatment. Progression, stability, or improvement in HRCT findings and changes in PFT parameters were analyzed. Continuous variables and categorical variables were analyzed using the t-test and chi-square test, respectively, for statistical comparisons. Results After 12 months, 49.1% of patients in the observation group exhibited improvement in HRCT findings, compared to none in the control group, in which 84.6% of individuals exhibited progression. PFT findings improved in the observation group, whereas they significantly declined in the control group (p < 0.001). Patients treated with tetrandrine for more than 6 months experienced greater improvements in HRCT findings and pulmonary function than those in the control group. Adverse reactions to tetrandrine, including facial pigmentation and liver function abnormalities, were mild. Conclusions Tetrandrine significantly mitigated HRCT-detected disease progression and lung function decline in patients with artificial stone-associated silicosis, particularly after prolonged treatment. These findings suggest that tetrandrine may serve as a viable therapeutic option for managing artificial stone-associated silicosis.